(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this writing is to present a comparative study of Haryanvi dialects. Comparative study conveys as many insights as possible into differences and similarities among the dialects being compared. Furthermore, the study also revealed that Haryanvi dialects follow the same pattern of Hindi language, it is also a study, How some facts come on the surface in comparison of dialects. This comparative study of Haryanvi dialects is to be done on the basis of phonological and morphological levels. Though some scholars including Dr. Grierson have named it ‘Bangru’. Infect Bangru is a dialect of Haryanvi language. At present Haryanvi is spoken in all over Haryana as well as southern-western parts of Punjab and those areas of Delhi neighboring Haryana. Traditionally Haryanvi has been the dominant mother tongue of the people of Haryana.